Culture-dependent and -independent methods revealed an abundant myxobacterial community shaped by other bacteria and pH in Dinghushan acidic soils - Wang, Chunling (PLoS One, 2020)
Myxobacteria are one of the most promising secondary metabolites producers. However, they are difficult to isolate and cultivate. To obtain more myxobacteria and know the effects of environmental factors on myxobacterial community, we characterized myxobacterial communities in Dinghushan acidic forest soils of pH 3.6–4.5 with culture-dependent and -independent techniques, and analyzed environmental factors shaping myxobacterial communities. A total of 21 myxobacteria were isolated using standard cultivation methods, including eleven isolates of Corallococcus, nine isolates of Myxococcus and one isolate of Archangium, and contained three potential novel species. In addition, a total of 67 unknown myxobacterial operational taxonomic units (OTUs) were obtained using high-throughput sequencing method. The abundance of Myxococcales account for 0.9–2.2% of bacterial communities, and Sorangium is the most abundant genus (60.1%) in Myxococcales. Correlation analysis demonstrated that bacterial diversity and soil pH are the key factors shaping myxobacterial community. These results revealed an abundant myxobacterial community which is shaped by other bacteria and pH in Dinghushan acidic forest soils.